Mind Mapping Pencegahan Fraud Dana Desa: Sebuah Studi Bibliometrik - Ardiansyah Ardiansyah; Jasmin Najwa Purmudi; Riska Dwi Savitri; Siti Hardianti (Universitas Riau Kepulauan, 2026)
This study examines the development of scientific literature regarding the prevention of village fund fraud using a bibliometric study approach. The body of literature on fraud prevention is growing rapidly, particularly in public sector accounting. Data were obtained from 75 scientific articles sourced from the Google Scholar database, covering publications from 2017 to 2026, using a combination of relevant thematic keywords. The analysis was conducted using VOSviewer software through two visualization methods, namely network visualization and density visualization, to identify research clusters, temporal trends, and topic density within the literature. Based on the integrated results of five types of VOSviewer visualizations (network visualization, overlay visualization, density visualization, citation network, and citation density), it can be concluded that research on the prevention and detection of fraud in the management of village funds has a robust, integrated scientific structure and is undergoing dynamic development.